Antibacterial Activity of Acetone and Ethyl Acetate Leaves, Stems and Rhizomes Extract of White Water Lily (Nymphaeae alba) Against Staphylococcus aureus and Escherichia coli - Mariam Ulfah; Ade Irawan; Teguh Adiyas Putra (Universitas Muhammadiyah Magelang, 2019)
White water lily (Nymphaeae alba) is one of the aquatic plants that is often used for traditional medicine. This plant has anticancer and antioxidant activity. The final result of this experiment is to determine the antibacterial activity of acetone and ethyl acetate extract from several parts of this plant, including leaves, stems and rhizomes againts several types of bacterial including Staphylococcus aureus and Escherichia coli. Kirby-Bauer diffusion Disc method is used in this study. Simplicia of leaves, stems and rhizomes of white water lily were macerated with acetone and ethyl acetate for 3 x 24 hours. Antibacterial tests were carried out to acetone and ethyl acetate leaves, stems and rhizome extract of white water lily. Amoxicillin was used as a positive control and dimethyl sulfoxide (DMSO) with concentration 20% as a negative control. The extract and amoxicillin were diluted with 20% DMSO. Each disk contained 100 µg of extract and 10 µg of amoxicillin. Antibacterial tests that have been carried out show that the acetone extract of leaves, stems and rhizomes white water lily has the highest attack value against bacteria, the diameter of the inhibition zone is 20 mm against S. aureus Acetone and ethyl acetate leaves, stems and rhizomes extract of white water lily did not have inhibitory effect on E. coli.